Upaya Guru Madrasah Ibtidaiyah dalam Meningkatkan Kualitas Pembelajaran Sejarah Kebudayaan Islam - Munawir, Munawir; Mujaroh Putri, Alvia Amalani; Amaliah, Rizky (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The history of Islamic culture is a type of Islamic education which in the learning process often faces several problems both in terms of strategies, methods and the media used. With several problems being faced, efforts are needed to overcome them. The purpose of this research is to describe SKI learning at Madrasah Ibtidaiyah and the teacher's efforts in planning and implementing learning in the classroom. This research uses a method (literature review) with a qualitative approach. The results of the research show that efforts can be made by educators to improve the quality of learning the history of Islamic culture by using appropriate methods and media during learning so that students can be enthusiastic and easily understand the material presented by teachers in learning the history of Islamic culture. The appropriate methods are lectures, drills, recitations and discussions. Media that can be used in SKI learning include PPT (Powerpoint) and educational games (Quizizz).